Creutzfeldt‐Jakob disease. Issue 2 (28th December 2016) - Iwasaki, Yasushi
Abstract : This review will explore the clinical and pathological findings of the various forms of Creutzfeldt‐Jakob disease (CJD). Clinical findings of CJD are characterized by rapidly progressive cognitive dysfunction, diffusion‐weighted magnetic resonance imaging (DWI) hyperintensity, myoclonus, periodic sharp‐wave complexes on electroencephalogram and akinetic mutism state. Neuropathologic findings of CJD are characterized by spongiform changes in gray matter, gliosis—particularly hypertrophic astrocytosis—neuropil rarefaction, neuron loss and prion protein (PrP) deposition. The earliest pathological symptom observed by HE staining in the cerebral cortex is spongiform change. This spongiform change begins several months before clinical onset, and is followed by gliosis. Subsequently, neuropil rarefaction appears, followed by neuron loss. Regions showing fine vacuole‐type spongiform change reflect synaptic‐type PrP deposition and type 1 PrP Sc deposition, whereas regions showing large confluent vacuole‐type spongiform changes reflect perivacuolar‐type PrP deposition and type 2 PrP Sc deposition. Hyperintensities of the cerebral gray matter observed in DWI indicate the pathology of the spongiform change in CJD. The cerebral cortical lesions with large confluent vacuoles and type 2 PrP Sc show higher brightness and more continuous hyperintensity on DWI than those with fine vacuoles and type 1 PrP Sc . CJD cases showing diffuse myelin pallor of cerebral white matter have been described as panencephalopathic‐type, and this white matter pathology is mainly due to secondary degeneration caused by cerebral cortical involvement, particularly in regard to neuron loss. In conclusion, clinical and neuroimaging findings and neuropathologic observations are well matched in both typical and atypical cases in CJD. The clinical diagnosis of CJD is relatively easy for typical CJD cases such as the MM1‐type. However, even in atypical cases it seems that clinical findings can be used for an accurate diagnosis.